2017
DOI: 10.18203/2349-2902.isj20173729
|View full text |Cite
|
Sign up to set email alerts
|

Ilio inguinal neurectomy in inguinal hernia

Abstract: Background: Inguinal hernia is one of the most common surgery done in any hospital. Chronic inguinal pain is one of the common problem these patients complain of. This study aims at evaluating the long-term outcomes of neuralgia and paraesthesia following routine ilioinguinal nerve division, compared to nerve preservation when performing Lichtenstein’s inguinal hernia repair.Methods: The present study is a randomized controlled trial of 60 cases of inguinal hernias admitted in General Surgery Department in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…While the oldest was 78 and 72 years in both the neurectomy group and the nerve preservation group, respectively. 17 Sunkar et al reported that 8% of his patients aged between 15-30 years and 34% aged between 61and 75 years old. 18 Saravanan et al reported that most of his patients aged between 31 to 40 years in both groups followed by 41 to 50 years.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…While the oldest was 78 and 72 years in both the neurectomy group and the nerve preservation group, respectively. 17 Sunkar et al reported that 8% of his patients aged between 15-30 years and 34% aged between 61and 75 years old. 18 Saravanan et al reported that most of his patients aged between 31 to 40 years in both groups followed by 41 to 50 years.…”
Section: Discussionmentioning
confidence: 96%
“…Mohanapriya et al reported a similar result and stated that pain at rest was present in 10% of his patients in the nerve preservation group after 8 months and it was statistically insignificant. 17 Also Saravanan et al reported that at one-month pain at rest was found in only one patient in the neurectomy group against six patients in the nerve preserving group, while after 6 months none of the neurectomy group felt pain at rest while 3 patients of the other group were still feeling pain at rest. 19 On the other hand, Neogi et al reported that the mean of group A patients of 0.6 was less than group B (1.05) showing that postoperative pain after one month in group A was less than group B.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations